Pelatihan Dan Pendampingan Membuat Media Pembelajaran Berbantuan Aplikasi Canva di SMP Negeri 3 Percut Sei Tuan - Sihotang, Siti Fatimah; Rusmini; Mazaly, Muhammad Rizky; Zuhri; Fadila; Kayla Khairani (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2023)
Canva application is an online application-based digital platform that can be used and developed by teachers in the process of creating interesting learning media for students. The Canva application also offers many features and templates that support Canva's appearance to be more interactive and easier to understand.. One of real benefits of Canva application for the education sector is exploring the creativity of educators and students in the teaching and learning process. In other words, training and mentoring activities to create learning media with the help of using the Canva application are useful in increasing creativity of teachers and students in creating learning media and operating the various features available. This needs to be done so that when making teaching materials, the results obtained are more interesting, thereby encouraging good learning outcomes in the teaching and learning process. The use of literature theories and concepts as a result of literature studies using quantitative methods is a type of research method used in community service activities. The results of community service activities show that there has been a significant increase in understanding for all participants in terms of creating learning media with the help of the Canva application. These results are supported by the participants' ability to complete the assignments given by the team of presenters and the results of calculating teacher responses regarding the benefits of training in making learning media using the Canva application obtained an average combined percentage is 96.08%, which results are included in very good category.